Decompression at 1.3 versus 1.6 bar and Nitrogen Elimination and Venous Gas Emboli : A Randomized Controlled Trial - Plogmark, Oscar; Hjelte, Carl ; 0009-0009-5522-8735; Olsson, Max ; 0000-0002-0437-3168; Ekström, Magnus ; 0000-0002-7227-5113; Frånberg, Oskar (Undersea & hyperbaric medicine : journal of the Undersea and Hyperbaric Medical Society, Inc, 2025)
INTRODUCTION: The optimal depth for decompression stops is unclear. We hypothesize that a decompression stop at 1.3 bar, compared with 1.6 bar, decreases post-dive whole-body nitrogen washout volumes and venous gas emboli (VGE). METHODS: In this randomized crossover trial, divers performed wet air dives of 40 minutes at 3.4 bar (340 kPa) with a seven-minute-long decompression stop at either 1.3 bar (Deco 1.3) or 1.6 bar (Deco 1.6) in randomized order. The primary outcome was the difference in post-dive whole body nitrogen washout volume, analyzed using multilevel linear regression. The secondary outcome was the difference in peak VGE detected by cardiac two-dimensional ultrasound, graded using the Eftedal-Brubakk scale, and analyzed with Wilcoxon matched-pairs signed-rank tests. RESULTS: Sixteen divers completed both Deco 1.3 and Deco 1.6. Post-dive whole body nitrogen washout volumes were measured in eight of the 16 participants and were lower with Deco 1.3 than Deco 1.6 (696 ml [95% confidence interval [CI], 601 to 790] versus 1068 ml [95% CI, 962 to 1174]), mean difference of 373 ml (95% CI, 243 to 502). Deco 1.3 had lower peak bubble grades than Deco 1.6 (interquartile range 2-3 versus 3-4; P=0.005), but the median grade was the same at 3. CONCLUSIONS: Decompression stop at 1.3 bar instead of 1.6 bar decreased post-dive whole body nitrogen washout volume and VGE. These findings may inform the development of future decompression models.
Copyright© Undersea and Hyperbaric Medical Society.
Keywords: Humans; Embolism, Air/prevention & control; Nitrogen/metabolism; Male; Diving/physiology; Adult; Decompression/methods; Cross-Over Studies; Female; Time Factors; Decompression Sickness/prevention & control; Middle Aged; Ultrasonography; Linear Models